2022
DOI: 10.3390/geomatics2030020
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Using Green Laser in Monitoring Local Scour around Bridge Pier

Abstract: Scour around bridge piers is considered as one of the major factors which causes failure of bridges in the United States. An undetected scour can affect the stability of the bridge, eventually leading to the collapse of the bridge. The experimental investigation of scour around a pier using a non-contact measuring method is carried out in this research. A green laser-based non-contact ranging technique is performed on a prefabricated scour hole to study the factors influencing the ability to reconstruct the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Scour needs to be monitored in a timely manner as around 80% of the railroad and highway bridges in the US are built over water bodies [1,2]. Natural disasters like earthquakes associated with heavy rain and flooding can severely damage bridges [3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Scour needs to be monitored in a timely manner as around 80% of the railroad and highway bridges in the US are built over water bodies [1,2]. Natural disasters like earthquakes associated with heavy rain and flooding can severely damage bridges [3].…”
Section: Introductionmentioning
confidence: 99%
“…Scour around bridge piers are usually measured using in-contact and non-contact scour measuring devices. Some examples of in-contact sensors include float-out devices, tethered buried switches, piezoelectric sensors, buried rods, and radar devices [2,7]. A float-out device measures the scour when it is disconnected from the ground.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent and successful study managed to locate and measure scour depths by combining SONAR data and a deep convolutional network [10]. Furthermore, it was revealed that although it performs worse in high turbidity, green laser technology was able to detect scour around bridge piers in an economic and safe way [11].…”
Section: Introduction and Background-scour Identification Approachesmentioning
confidence: 99%